2021
DOI: 10.3390/rs13193957
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Target Detection in Spaceborne–Airborne Collaborative SAR Images via Proposal and Polarization Fusion

Abstract: This paper focuses on vessel detection through the fusion of synthetic aperture radar (SAR) images acquired from spaceborne–airborne collaborative observations. The vessel target detection task becomes more challenging when it features inshore interferences and structured and shaped targets. We propose a new method, based on target proposal and polarization information exploitation (TPPIE), to fuse the spaceborne–airborne collaborative SAR images for accurate vessel detection. First, a new triple-state proposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…Few studies have been reported on W-band (75 ~110 GHz) Existing systems usually have a co-linear polarization transceiver. Using multiple polarization imaging can obtain more information of observation scenes Guo et al [16]; Cheng et al [17]; Zhu et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been reported on W-band (75 ~110 GHz) Existing systems usually have a co-linear polarization transceiver. Using multiple polarization imaging can obtain more information of observation scenes Guo et al [16]; Cheng et al [17]; Zhu et al [18].…”
Section: Introductionmentioning
confidence: 99%